ANALYTIC CAUSATIVES IN JAVANESE: A LEXICAL- FUNCTIONAL APPROACH - Agus Subiyanto (PAROLE: Journal of Linguistics and Education, 2013)
Analytic  causatives  are  the  type  of  causatives  formed  by  separate predicates  expressing the cause and the effect, that is, the causing notion  is  realized  by  a  word  separate  from  the  word  denoting  the caused activity. This paper aims to discuss the forms and syntactic structure  of  analytic  causatives  in  Javanese.  To  discuss  the syntactic structure, the theory of lexical functional grammar (LFG) is  employed.  The  data  used  in  this  study  is  the  „ngoko‟  level  of Javanese of the Surakarta dialect. By using a negation marker and modals  as  the  syntactic  operators to test mono-  or bi-clausality  of analytic  causatives,  the  writer  found  that  analytic  causatives  in Javanese form biclausal constructions. These constructions have an X-COMP  structure,  in  that  the  SUBJ  of  the  second  verb  is controlled  by  the  OBJ  of  the  causative  verb  (N)gawe  „make‟.  In terms  of  the  constituent  structure,  analytic  causatives  have  two kinds of structures, which are V-cause OBJ X-COMP and V-cause X-COMP OBJ. Kausatif  analitik  adalah  tipe  kausatif  yang  dibentuk  oleh  dua predikat  atau  dua  kata  terpisah  untuk  mengungkapkan  makna sebab dan akibat, yakni makna sebab direalisasikan oleh kata yang berbeda  dengan  kata  yang  menyatakan  makna  akibat.  Tulisan  ini membahas  bentuk  dan  struktur  sintaksis  kausatif  analitik  dalam bahasa Jawa. Untuk menjelaskan struktur sintaksis digunakan teori Tata  Bahasa  Leksikal  Fungsional.  Data  yang  digunakan  dalam penelitian  ini  adalah  bahasa  Jawa  dialek  Surakarta  ragam  ngoko. Dengan  menggunakan  alat  uji  pemarkah  negasi  dan  penggunaaan modalitas,  penulis  menemukan  bahwa  kausatif  analitik  dalam bahasa Jawa membentuk struktur biklausa. Konstruksi ini memiliki struktur  X-KOMP,  yakni  SUBJ  dari  verba  kedua  dilesapkan  dan dikendalikan  oleh  OBJ  dari  verba  kausatif  (N)gawe  „membuat‟. Dalam  struktur  konstituen,  analitik  kausatif  memiliki  dua  macam bentuk, yakni  V-kuasatif OBJ X-COMP and V-kausatif X-COMP OBJ.